Strategi Kepala Pesantren Dalam Meningkatkan Ubudiyah Santri - Moh. In’am Jamaluddin (Pedir Research Institute, 2022)
This study is aimed to determine 1). the strategy of the head of the pesantren (Islamic boarding school) and 2). the obstacles faced in improving the ubudiyah (Islamic boarding school routines) of students at Nurul Ummah Pacet Mojokerto, Male Campus 1. This research belongs to qualitative one with a field research approach. Sources of data are in the form of primary data taken from the main source and secondary data were created by other parties. Data collection techniques are interviews, observation and documentation. The data analysis technique used is data reduction, data presentation and concluding. The results showed that first, the strategy of the head of the pesantren refers to the visions of the Islamic boarding school and is realized in a program oriented to the formation of worship characters through (a) knowing, trying to understand the concept of ubudiyah in theory, (b) loving, instilling a love for ubudiyah with the principle of exemplary, and (c) acting, doing habituation by providing escort and conditioning. Second, the obstacles faced are the limited infrastructure and the unbalanced ratio between escort officers and the number of students.